Corporate Governance and Financial Performance of Quoted Manufacturing Companies in Nigeria - Akingunola, Richard Ore-Oluwa; Olaniyan, Joshua D.; Soyemi, Kenny Adedapo (NIU Journal of Social Sciences, 2018)
This study explored the effect of corporate governance mechanisms and financial performance of quoted manufacturing companies in Nigeria using 50 listed manufacturing companies on the Nigerian Stock Exchange market within the period of 5 years 2009-2013. The study used six key variable for corporate governance while Return on Assets and Return on Equity were used as a measurement of performance. Based on a regression analysis, results shows that women on board of directors (BWN), number of executive directors (NED) and number of non-executive directors (NNED) have direct relationship with ROA, and these conform with  aâ€™priori expectation. However, only number of directors (NDTS) reported a negative significant impact on ROA. On the part of return on equity (ROE), only of executive directors (NED) reported a positive significant impact on ROE. This study recommended that; industry specific effects should be taken into consideration before formulating codes of corporate governance that determine the characteristics of the board structure. Keywords: Audit Committee, Board of Director, Corporate Governance, Profitability, Performance